A case report of ventricular septal defect complicating transcatheter aortic valve implant for aortic regurgitation: novel complication and technical considerations. Issue 10 (5th October 2021) - Hartnett, Jack; Brandon, Lisa; Waterhouse, Deirdre; Murphy, Ross T; Walsh, Kevin P; Spence, Mark S; Maree, Andrew O
Abstract: Background: Transcatheter aortic valve implantation (TAVI) has proven efficacy in the treatment of aortic stenosis (AS). Understandably, there is increasing enthusiasm for its use to treat aortic regurgitation (AR). However, there are significant anatomical differences between AS and AR which make TAVI for AR more complex. Case summary: We present the case of technically challenging TAVI for severe AR, which was complicated by a traumatic ventricular septal defect (VSD) that required percutaneous closure. To our knowledge, this is the first published case of VSD post-TAVI for AR. Discussion: This unanticipated complication highlights anatomical differences between TAVI use in AS and AR. Lack of aortic valve calcification and excessive annular compliance made stable deployment of a self-expanding valve extremely challenging. Despite device oversizing, repeated embolization of the prosthesis into the left ventricular outflow tract traumatized the interventricular septum.